Efecto del Capital Humano en las Exportaciones de Productos de Alta Tecnologia; Evidencia para América Latina y la Unión Europea, periodo 2000-2016 - Jiménez Luzón, Gloria Cecibel (2020)
The technology innovations have served to reach levels of competitiveness in international markets, and for this reason the technology is a very important factor in order to influencer in the increase of competitiveness for countries or regions. This research analyzes the effect human capital on exports of high-tech products to Latina America and European Union, during 2000-2016, including 18 and 22 countries respectively. The research has like dependent variable the exports of high-tech products, the independent variable is human capital, and I added control variables such as foreign direct investment and industry. The results of generalized least squares (GLS) model show a positive relationship between exports of high-tech product and human capital, however, this relationship is negative for Latin America when adding control variables. Finally, as a complement to the analysis, through Pedroni (1990) and Westerlund (2007) tests determine the existence of a short-term and long-term equilibrium relationship between variables at global and regional levels. According the results obtained, we have some implications and policy recommendations that the regions studied can improve or implement, which are aimed at macroeconomic and financial stability policies, as well as improve in the education sector through quality education, scientific and technological advances.